A Multinational Study of Teachers' Codes of Ethics: Attitudes of Educational Leaders. (March 2020) - Shapira-Lishchinsky, Orly
The study aimed to elicit a universally accepted meaning of "ethical practice in school" from teachers' codes of ethics formulated by educational leaders including school principals, the nation's government, and teachers' union representatives. Analysis was based on a random sample of 30 codes of ethics in various countries using a qualitative methodology. The findings generated a multidimensional model. School principals' access to this model may advance making decisions that foster an ethical school environment worldwide.